Expression Collagen I and III in Anterior Vaginal Women with and without Pelvic Organ Prolapse - Basyar Basyar; Trika Irianta; Syahrul Rauf (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: To find out the expression of collagen [ and III in the anterior vaginal wall of women with and without pelvic organ prolapse (POP). Method: The research was a cross sect ional study, conducted in Dr. Wahidin Sudiro Husodo hospital and its networks from January 1, 2011 to April 1, 2012. The case group consisted of 35 women with POPlevel III and IV.The contro l group consisted of35 women without POP. The expression of collagen I and III were examined by immunohistochemical test with the stain ing of antibody of collagen I (mouse monoclonal collagen lab 90395 ) and the antibody collagen III (Mu167 4i).The data was then analyzed by using a computer statistic program with a significance level of 0.05. Result: It was found that in the group of women with POP, there were 28 cases of expression collagen III (84%), which is significantly higher than in women without POP, found in only 20 cases (58.8%), with p=0.02. Meanwhile, in the group of POP, 9.1% of subjects showed moderate expre ssion of collagen I, significantly less compared to the expressio n in the contro l group (35.3%), with p=0.007. For the ratio of collagen I and III, the result was weak in women with POP(58.5% ) while in the control group, the result was high (85.7%). Conclu sion: In terms of collagen I and III expression, there was no significant difference between the two groups. Keywords: collagen I, collagen III, pelvic organ prolapse, vaginal wall